Analysis of the Influence of Work Stress and Work Culture on Employee Performance - Mubarok, Isyroqul; Safutri, Jemmy Nova Euis; Gideon, Andrea; Sugiarti, Rini; Suhariadi, Fendy (International Journal of Education, Information Technology, and Others, 2024)
In facing the era of globalization and increasing business competition, attention to employee performance becomes crucial. In this context, work stress and work culture become the primary focus of research. This literature review utilizes the literature study method to investigate the impact of work stress and work culture on employee performance. Work stress, arising from high pressure and uncertainty in the work environment, is examined in the context of its effects on psychological well-being and employee productivity. In line with that, the role of work culture, encompassing values, norms, and beliefs within the organization, is explained in the context of its influence on employee motivation and performance. Through the literature study method, this research presents key findings from previous studies to provide a deep understanding of the complexity of the interaction between work stress, work culture, and employee performance. These findings are expected to contribute to practical and theoretical insights into human resource management strategies in this era of globalization, where emphasis on stress management and the development of positive work culture is imperative for achieving optimal employee performance.